O médico residente e o estudante de medicina frente à terminalidade da vida: uma análise das atitudes e conhecimentos sobre o processo morte e morrer - Gonçalves, Kelly Carvalho Silveira (2019)
In the field of medicine, professionals and students routinely deal with terminal patients and, compulsorily, are exposed to death and the dying process. In addition, the ability of medical science to prolong life with the use of technology has increasingly generated questions about how much the physician should maintain the treatment of terminal patients. This research consists of a cross- sectional, analytical study with a quantitative approach, and in the application of a questionnaire to the students of the fifth and ninth semesters of Medicine of the Federal University of Santa Maria and residents of Medical Clinic, Surgery and Anesthesiology, active in the University Hospital of Santa Maria. The objective, following the analysis of the data, of verifying the positioning, attitudes and previous knowledge about the process death and dying in the medical student and in the resident physician. As a result the following considerations were obtained: Students understand that orthothanasia is a legalized procedure, understand death as the end of a natural cycle, in the final terms of the course they take part in discussions about the death process, start talking to their relatives about their own finitude, they mention having sufficient knowledge about palliative sedation, they feel prepared to deal with the death of their patients and begin to disagree more strongly with the practice of dysthanasia. However, they affirm that the training did not contribute to a preparation for coping with death, they report not having sufficient knowledge about vital testament, do not believe that even before being informed the patient knows the severity of his case and they stop believing that the patient can get worse after the bad news. Significant factors were: having experience in ICUs, having more than 25 years and not having religion, to avoid with greater conviction the practices of dysthanasia. Through these results it is understood that there has been some progress as the course of Medicine in relation to the understanding of death, in the sample studied, despite the persistence of some knowledge gaps. It is also questioned whether such progress is limited to theory or extravasa for medical practice, confirming itself through decisions that evoked "good death", as would be ideal.